2017
DOI: 10.1002/jcb.26199
|View full text |Cite
|
Sign up to set email alerts
|

Swiprosin‐1: Its Expression and Diverse Biological Functions

Abstract: Swiprosin-1/EFhd2 is a Ca 2þ binding adapter protein involved in the various cellular functions. Swiprosin-1 is significantly upregulated in a number of pathological conditions of inflammation, neurodegeneration, and cancer. Swiprosin-1 associated with actin and its expression level amplifies the production of proinflammatory mediators and modulates the activation of transcription factor during immune cells activation. This review aims at providing an overview of the expression and function of swiprosin-1/EFhd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…High expression levels of ST13 are associated with reduced cell migration and proliferation of colorectal cancer cells (62). Swiprosin 1, which is involved in cortical cytoskeleton dynamics among other functions (63,64), was also decreased in the spleen after 48 h of kynurenine administration (ratio −1.14).…”
Section: Mass Spectroscopy; Prolonged (48 H) Groupmentioning
confidence: 99%
“…High expression levels of ST13 are associated with reduced cell migration and proliferation of colorectal cancer cells (62). Swiprosin 1, which is involved in cortical cytoskeleton dynamics among other functions (63,64), was also decreased in the spleen after 48 h of kynurenine administration (ratio −1.14).…”
Section: Mass Spectroscopy; Prolonged (48 H) Groupmentioning
confidence: 99%
“…However, it promoted metastasis in B16F10 cells. 48 Taken together, these data suggested that STC2 promoted CRC progress by regulating a group of target genes.…”
Section: Discussionmentioning
confidence: 85%
“…In total, 25 rare variants show allelic imbalance biased toward the deleterious alternative allele (20 splice and 5 stop-gain). Among those, one variant is in EFHD2, a gene coding for Ca 2+ adapter protein involved in B-cell apoptosis, NF-kB mediated inflammatory response, and immune cell activation and motility [30][31][32][33]. The carrier of this event was diagnosed with idiopathic cardiomyopathy, where accompanying symptoms (elevated inflammatory markers, Raynaud's disease, and alopecia) are indicative of auto-immune issues.…”
Section: Allele-specific Expression Outliers In Rare Disease Casesmentioning
confidence: 99%